A ludicidade como possibilidade pedagógica para o letramento científico a partir de percepções docentes - Lima, Tatieli Trindade (2023)
Every teaching process that values the ludic aspect becomes interesting and motivating so that students' learning develops in an effective and meaningful way. Thus, this research aimed to investigate the perceptions of teachers in the field of Natural Sciences in view of the contribution of playfulness as a pedagogical possibility for the LC through a case study developed in three public schools in the city of Uruguaiana/RS. As for the research subjects, it is a group of six Natural Sciences teachers from the Final Years of Elementary School. For data collection, instruments such as questionnaires prepared on the Google Forms platform and semi-structured interviews on the Google Meet platform were used. For data analysis, an approximation with Discursive Textual Analysis (DTA) (MORAES; GALIAZZI, 2007) and the levels of scientific literacy proposed by Ruppenthal, Coutinho and Marzari (2020) were sought. As results regarding the teachers' perceptions about ludicity, we could see that they relate it to games and games and to practical activities in Natural Sciences. They perceive playfulness as an ally for meaningful learning and see it as a pedagogical possibility for the LC, as it provides an interesting and motivating teaching and learning process. It was also noticed the need for teacher training to search for new methodological strategies, as we still see traditional teaching methods that add little to the construction of students' scientific knowledge, with teacher training being one of the main paths for the changes that are made necessary in Science Teaching. The teacher training meetings also allowed us to bring the University and the school closer together, as it provided relevance to the different views of the teachers who, based on their professional experiences, know the real needs of Science Teaching in Basic Education.